Erythroderma (exfoliative dermatitis). Part 1: underlying causes, clinical presentation and pathogenesis. (1st August 2021) - Tso, S.; Satchwell, F.; Moiz, H.; Hari, T.; Dhariwal, S.; Barlow, R.; Forbat, E.; Randeva, H.; Tan, Y. T.; Ilchyshyn, A.; Kwok, M. M.; Barber, T. M.; et al.
Summary: Erythroderma (exfoliative dermatitis), first described by Von Hebra in 1868, manifests as a cutaneous inflammatory state, with associated skin barrier and metabolic dysfunctions. The annual incidence of erythroderma is estimated to be 1–2 per 100 000 population in Europe with a male preponderance. Erythroderma may present at birth, or may develop acutely or insidiously (due to progression of an underlying primary pathology, including malignancy). Although there is a broad range of diseases that associate with erythroderma, the vast majority of cases result from pre‐existing and chronic dermatoses. In the first part of this two‐part concise review, we explore the underlying causes, clinical presentation, pathogenesis and investigation of erythroderma, and suggest potential treatment targets for erythroderma with unknown causes. Abstract : Click here for the corresponding questions to this CME article.